Additive manufacturing (3D printing): a new approach for the manufacture of individualized medicines - Figueiredo, Sara (2021)
Abstract of poster presented at the Congresso Nacional dos Farmacêuticos 2020 e XIV Congresso Mundial dos Farmacêuticos de Língua Portuguesa, Virtual, 26-28 november 2020